Characteristic differences in the choice of factors of a healthy lifestyle as components of the individual physical culture of modern schoolchildren - Oksana Marchenko (Kharkiv State Academy of Physical Culture, 2018)
The article describes the factors of a healthy lifestyle, which adhere to students of different ages. Purpose: to explore the age-related features of the formation of the factors of a healthy lifestyle as components of individual physical education of schoolchildren of 11-17 years old. Material & Methods: 628 people took part in the study (282 young men; 346 women). In order to solve the research problems, a survey was conducted of respondents "Determining the motives and interests of schoolchildren in the field of physical culture and sports". Results: it has been determined that motor activity, as one of the main factors of a healthy lifestyle in boys and girls aged 14-17, remains in the last place, except for sports class students. It is proved that only 34,1% of graduates, 48,9% of students in the 9th grade and 33,3% of ten students do not use alcoholic beverages. The highest percentage among smokers is in the 7th and 8th grades (33,3% and 22,7% respectively). Young men graduates are more likely to have a healthy lifestyle, and the percentage of those who smoke is reduced to 14,6%. Among the girls, it was found that 23,3% of ninth-graders smoke. Conclusion: it is proved that in the age aspect there are quite significant differences between the boys and girls in choosing the priority factors of a healthy lifestyle, which they adhere to during the week. Attitudes towards bad habits are also different and ambiguous. That is, with age, the priorities of the value orientations of young people change, and the gender factor influences the formation of young men and women's views on maintaining a healthy lifestyle.